Implementation of SVM based Matrix Converter with Wind turbine and DFIG - Sathya Prishma.J, Uma.J (International Journal of Advanced Science and Technology, 2020)
Renewable energy source connected to Grid includes Doubly fed induction generator and space vector switching of Matrix converter is proposed. The conventional converter recognized as voltage source converter connected in reverse way is replaced by Matrix Converter. A strategy is equipped for switching of matrix converter is SVM techniques. The ISVM scheme, Matrix converter regulate the current and output voltage and to maintain the unity power factor. The Maximum Power extraction is achieved by using MPPT algorithm such as P&O algorithm. Keywords: Wind Energy Conversion System (WECS);Doubly fed induction Generator (DFIG);Direct matrix converter (DMC).